Empress Court - Ghosh, Ayan (Jio Institute, 2023)
Empress Court,132 Maharshi Karve Road, Churchgate. The Mehta family bought the property in 1960 from a Parsi family. Currently, Empress Court serves as the residence of the fourth generation of the Mehta family.